The quest : Haywood Hansell and American strategic bombing in World War II - Griffith, Charles (Air University Press, 1999)
This biography of Maj Gen Haywood S. Hansell Jr. provides an in-depth look at the life and career of one of airpower's pioneer thinkers. General Hansell's professional life was devoted to the theory and practice of strategic airpower₇the single most controversial military debate of the twentieth century. Hansell believed that wars could and should be won through precision bombing of military and industrial/commercial targets, a theory and practice that the United States Army Air Forces abandoned during World War II because of the dictates of existing technology, the demands of combat, and the fact that the passions of war swept away any moral concerns involving strategic bombing. Nevertheless, Hansell's main contribution to air doctrine was the concept that through selective targeting and an ability to place the bombs on those targets, airpower could win wars by crippling an enemy's ability to supply his forces and without causing wanton death and destruction. The author believes that the Persian Gulf War went a long way toward proving Hansell's theories to be correct